1883 Ill. Rev. Stat. 453 - (:unkn) unknown (My University, 1879)
§ 56: Prohibited the concealed carry of any pistol, knife, slungshot, knuckles of brass, steel, iron, or other deadly weapons. Also prohibited brandishing said weapons. Violators fined not exceeding one hundred dollars.
Keywords: BRANDISHING; CARRY - CONCEALED